Public key encryption with conjunctive keyword search secure against keyword guessing attack from lattices. Issue 11 (22nd October 2018) - Mao, Yaojun; Fu, Xingbing; Guo, Chen; Wu, Guohua
Abstract: Public key encryption With keyword search (PEKS) enables a cloud server (CS) to get the search trapdoor to identify ciphertext containing the target keyword without decrypting the ciphertext or knowing the target keyword. With the advent of mobile cloud computing, PEKS has ushered in an era of new development opportunities and new challenges. In mobile cloud computing environment, the PEKS schemes demand strict bounded timing response and security. However, traditional PEKS schemes rely on heavy bilinear pairing computations, which causes a delay from the CS to the mobile terminal. Moreover, as computing power increases, PEKS is more vulnerable to suffer from an inherent insecurity known as inside keyword guessing attack, which leaks user data query information. To achieve a secure and efficient searchable encryption scheme in the mobile cloud computing environment, we put forward a lattice‐based searchable encryption scheme that supports conjunctive keyword search. Our scheme achieves higher computational efficiency and is resistant against quantum attacks compared with traditional PEKS schemes. To further enhance security and make our scheme secure against keyword guessing attack, we hide the decryption parameters by outsourcing part of the decryption process to a semitrusted third party called unusual keyword server, so that the CS cannot guess the exact keyword by performing consistency verification. Abstract : To achieve a secure and efficient searchable encryption scheme in the mobile cloud computing environment, we put forward a lattice‐based searchable encryption scheme that supports conjunctive keyword search. To further enhance security and make our scheme secure against keyword guessing attack, we hide the decryption parameters by outsourcing part of the decryption process to a semitrusted third party called unusual keyword server, so that the cloud server cannot guess the exact keyword by performing consistency verification.